Midline vs. lateral flank approach for spaying nutrias (Myocastor coypus) - Di Ianni, Francesco; Pelizzone, Igor; Gavezzoli, Martina; Fumeo, Martina; Vetere, Alessandro (Frontiers in Veterinary Science, 2025)
The nutria (Myocastor coypus), an invasive semi-aquatic rodent in Europe introduced for the fur and meat industry at the beginning of the 20th century, has rapidly become a significant ecological and economic concern. In Italy, the damage caused by nutrias to crops, wetlands, and drainage systems has prompted the development of containment plans. However, these efforts, while effective in the short term, are challenged by rapid recolonization and local resistance. One emerging approach for controlling nutria populations is sterilization. This study compared two surgical techniques for ovariectomy in 60 free-ranging nutrias: 30 animals underwent the flank approach (FA), and 30 underwent the ventral midline approach (VMA). The animals were randomly assigned to one of the two groups and monitored for anesthesia duration, surgery time, recovery, and return to feeding. Results indicated that the FA group exhibited significantly shorter surgical and recovery times than the VMA group, with a positive correlation between body weight and surgery duration only in the VMA group. Additionally, a higher percentage of animals in the FA group resumed feeding within 12 h, suggesting better post-operative recovery. The FA technique thus demonstrated advantages over the VMA, reducing the risk of intraoperative complications and shortening recovery times. These findings suggest that the FA technique may be more suitable for reproductive control of nutria as part of invasive wildlife management strategies.